New challenges in building fire safety. - Roque, Rolando G. (Philippine Engineering Journal)
As buildings grow higher and their uses become more complex, and as plastic based combustible loadings increase, building fires become a complex problem. Dramatic progress has been made in fire protection engineering. Unfortunately, our local building and fire codes have lagged behind the current technology. Direct code application may not be the best and most economical solution. Alternative solutions must be equal to or better than the code requirements. Building fire safety is not accomplished only by installing a sprinkler system, but must also include an egress system that affords an acceptable level of life safety, an alarm and detection system that is reliable, an effective smoke control system, an economical fire protection covering for structural members and a strategy for maximizing the capabilities and resources of the fire department. Integration of the various fire protection features is the new challenge in building fire safety.